SUSTAINABILITY ASSESSMENT OF SOCIAL FORESTRY IN THE SAGENA INDAH FOREST FARMERS GROUP - Hayatus Sa'adiah; Markum; Andi Chairil Ichsan (Forestry Study Program University Of Mataram, 2026)
Social Forestry (SF) under the Community Forestry (Hutan Kemasyarakatan/HKm) scheme promotes community-based forest management, whose sustainability largely depends on institutional capacity and forest management performance. This study aimed to evaluate the sustainability status of Social Forestry implementation in the Sagena Indah Forest Farmers Group (Kelompok Tani Hutan/KTH Sagena Indah), Kiantar Village, West Sumbawa Regency, Indonesia, using the Multi-Aspect Sustainability Analysis (MSA) framework. The assessment integrated Institutional Management and Area Management dimensions based on regulatory-derived sustainability attributes. Data were collected through field observations, document verification, and structured interviews with twelve purposively selected key persons representing four stakeholder groups. The MSA analysis was conducted using sustainability indexing, leverage analysis, future condition assessment, Monte Carlo simulation, and Random Iteration analysis. The results showed that KTH Sagena Indah achieved a Sustainable status, although sustainability performance differed between management components, with Area Management performing better than Institutional Management. The findings indicate that Social Forestry sustainability is shaped by the interaction between governance capacity, community participation, and forest management practices. Based on the findings, sustainability improvement should focus on strengthening priority attributes within Institutional Management and Area Management to achieve more balanced and sustainable Social Forestry implementation.